Animal thinking: local intelligences and aesthetics (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This article explores the relationship between aesthetics, art, and the animal world. To do so, it examines artists who have constructed their poetics based on animal ecosystems and the worlds surrounding them. This relationship with animal life implies a movement from representation to presentation, as the set of animal signs unfolds and inserts itself into the world of the arts. These perspectives are ecological and negentropic, as they propose a departure from the anthropocentric machine to discover the singularities of living beings with their own intelligences. Finally, we examine three artists who live in Guayaquil, who reinstate the practice of visual arts in previously unseen places. These artists explore the interaction with technology, the city's ecosystems, the extractivism inherent to the urban environment, and the lack of interspecies diplomacy that prioritizes the preservation of humans over the earth. Their proposals invite us to question our way of life and to experience the locality with its own logic, knowledge, and life solutions.
Keywords: aesthetics; animal thought; visual arts; cognitive ethology; intelligence of the territories